Noncanonical WNT‐5A signaling regulates TGF‐β‐induced extracellular matrix production by airway smooth muscle cells. Issue 4 (19th December 2012) - Kumawat, Kuldeep; Menzen, Mark H.; Bos, I. Sophie T.; Baarsma, Hoeke A.; Borger, Pieter; Roth, Michael; Tamm, Michael; Halayko, Andrew J.; Simoons, Mirjam; Prins, Alita; Postma, Dirkje S.; Schmidt, Martina; et al.
Abstract : Transforming growth factor β (TGF‐β), a key mediator of fibrotic responses, is increased in asthma and drives airway remodeling by inducing expression of extracellular matrix (ECM) proteins. We investigated the molecular mechanisms underlying TGF‐β‐induced ECM expression by airway smooth muscle cells and demonstrate a novel link between TGF‐β and Wingless/integrase 1 (WNT) signaling in ECM deposition. Airway smooth muscle expresses abundant WNT ligands, with the noncanonical WNT‐5A being the most profoundly expressed. Interestingly, WNT‐5A shows 2‐fold higher abundance in airway smooth muscle cells isolated from individuals with asthma than individuals without asthma. WNT‐5A is markedly induced in response to TGF‐β (4–16‐fold; EC50 0.3 ng/ml) and is required for collagen and fibronectin expression by airway smooth muscle. WNT‐5A engages noncanonical WNT signaling pathways, as inhibition of Ca 2+ and c‐Jun N‐terminal kinase (JNK) signaling attenuated this TGF‐β response, whereas the canonical WNT antagonist Dickkopf 1 (DKK‐1) did not. Accordingly, WNT‐5A induced JNK phosphorylation and nuclear translocation of nuclear factor of activated T cells c1 (NFATc1). Furthermore, silencing of the WNT‐5A receptors Frizzled 8 (FZD8 ) and RYK attenuated TGF‐β‐induced ECM expression. Collectively, these findings demonstrate that noncanonical WNT‐5A signaling is activated by and necessary for TGF‐β‐induced ECM production by airway smooth muscle cells, which could have significance in asthma pathogenesis.—Kumawat, K., Menzen, M. H., Bos, I. S. T., Baarsma, H. A., Borger, P., Roth, M., Tamm, M., Halayko, A. J., Simoons, M., Prins, A., Postma, D. S., Schmidt, M., and Gosens, R. Noncanonical WNT‐5A signaling regulates TGF‐β‐induced extracellular matrix production by airway smooth muscle cells. FASEB J. 27, 1631–1643 (2013). www.fasebj.org